Gendered Security Harms: State Policy and the Counterinsurgency Against Boko Haram - Elizabeth Pearson (African Conflict and Peacebuilding Review, 2020)
Scholars have critiqued the incorporation of gender into counter-terrorism and countering violent extremism: programmes have instrumentalised the Women Peace and Security (WPS) agenda towards state-centric goals and essentialised the women (and men) they encounter. Furthermore, as Huckerby outlines, the explicit inclusion of gender in security policy can produce specific gendered security harms: coercive and non-coercive practices; securitization of women’s rights; and lack of attention to the gendered effects of seemingly gender-neutral policy. This article engages Huckerby’s typology to explore the gendered security harms produced in Nigeria’s counter-insurgency against ‘Boko Haram’. It suggests first that a simplistic approach to women, not gendered power relations, leaves Nigeria unable to respond to the complex gendered dynamics of jihadist actors in the northeast. Second, a neglect of human rights and the role of state actors in abuses actively enable gendered security harms. The article concludes that Nigeria is therefore still failing to protect women.